On the problem of asteroid-comet hazard - Глущенко, А.А.; Медведев, Е.А.; Горелов, Д.Ю. (Radiotekhnika, 2017)
The probability of collision of hypothetical parent bodies of meteor streams and associations from the KNURE (5160 orbits) catalog with the Earth, taking into account changes in the orbital elements of the cosmic body during its evolution, is calculated. It is shown that most of the most dangerous streams have orbits of an asteroid type, and their potential parental bodies belong to the Atens asteroids.